2020
DOI: 10.2106/jbjs.oa.20.00045
|View full text |Cite
|
Sign up to set email alerts
|

Managing Resident Workforce and Education During the COVID-19 Pandemic

Abstract: Background: The novel coronavirus and associated Coronavirus Disease 2019 (COVID-19) is rapidly spreading throughout the world, with robust growth in the United States. Its drastic impact on the global population and international health care is swift, evolving, and unpredictable. The effects on orthopaedic surgery departments are predominantly indirect, with widespread cessation of all nonessential orthopaedic care. Although this is vital to the system-sustaining measures of isolation and resource … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
175
0
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(194 citation statements)
references
References 23 publications
4
175
0
15
Order By: Relevance
“…In order to limit patient exposure and team risk, we introduced a team cohort approach: a rotating small-team approach designed for each clinical site in our residency program as described by other surgical subspecialties. 4 Each cohort team is prevented from physical interaction with the other teams and cover separate days in the hospital. Faculty-resident partnerships were assigned to limit interaction between department members but provide comprehensive coverage at each clinical site.…”
Section: Team Cohortingmentioning
confidence: 99%
“…In order to limit patient exposure and team risk, we introduced a team cohort approach: a rotating small-team approach designed for each clinical site in our residency program as described by other surgical subspecialties. 4 Each cohort team is prevented from physical interaction with the other teams and cover separate days in the hospital. Faculty-resident partnerships were assigned to limit interaction between department members but provide comprehensive coverage at each clinical site.…”
Section: Team Cohortingmentioning
confidence: 99%
“…Hand in hand with ensuring adequate supply of PPEs, residency programs in the US divided resident task force into two groups and arranged resident rotations every fteen days. One group will be engaged in clinical activity and the second group will stay at home but will be involved in virtual teaching activities & consultations [9,10]. Naser et al reported experience of restructuring of general surgery residents during pandemics into three exclusive groups (inpatient, operative, and clinic) rotating weekly to practice appropriate physical distancing and reduce the possibility of transmission among residents [11].…”
Section: Residents Safetymentioning
confidence: 99%
“…Ethiopia has recorded its rst case in March and currently the number of infected people has escalated to more than 2000 [1]. The anticipated duration and impact of Covid-19 on the global population and international healthcare is swift, evolving, and unpredictable [2] In this unprecedented scenario, healthcare systems had to rapidly reshape their organization to cope with the emergency, aiming to optimize resources and minimize a further spread of the infection [3]. The daily responsibilities attributed to a resident demand a commitment to proper time management and the ability to prioritize tasks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations